Lipoxin A4 Regulates Lipopolysaccharide-Induced BV2 Microglial Activation and Differentiation via the Notch Signaling Pathway - Wu, Jun; Ding, Dan-hua; Li, Qian-qian; Wang, Xin-yu; Sun, Yu-ying; Li, Lan-Jun (Frontiers in Cellular Neuroscience, 2019)
Inflammatory responses contribute to the pathogenesis of various neurological diseases, and microglia plays an important role in the process. Activated microglia can differentiate into the pro-inflammatory, tissue-damaging M1 phenotype or the anti-inflammatory, tissue-repairing M2 phenotype. Regulating microglia differentiation, hence limiting a harmful response, might help improve the prognosis of inflammation-related nervous system diseases. The present study aimed 1. to observe the anti-inflammatory effect of lipoxin A4 (LXA4) on the inflammatory response associated to lipopolysaccharide (LPS)-induced microglia activation, 2. to clarify that LXA4 modulates the activation and differentiation of microglia induced by LPS stimulation, 3. to determine whether LXA4 regulates the activation and differentiation of microglia through the Notch signaling pathway, 4. to provide a foundation for the use of LXA4 for the treatment of inflammatory related neurological diseases. To construct a model of cellular inflammation, immortalized murine BV2 microglia cells were provided 200 ng/ml lipopolysaccharide (LPS). To measure the mRNA and protein levels of inflammatory factors (interleukin [IL]-1β, IL-10, and tumor necrosis factor [TNF]-α) and M1 and M2 microglia markers (inducible nitric oxide synthase [iNOS], cluster of differentiation [CD]32, arginase [Arg]1, and CD206), we performed quantitative reverse transcription polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA), immunofluorescence, or flow cytometry. To determine the mRNA and protein levels of Notch signaling components (Notch1, Hes1, and Hes5), we performed qRT-PCR and western blot. LXA4 inhibits the expression of Notch1 and Hes1 associated with M1 type microglial differentiation and decreases the M1 type microglia marker iNOS and related inflammatory factors IL-1β and TNF-α. Moreover, LXA4 upregulates the expression of the M2-associated Hes5, as well as the expression of the M2 microglia marker Arg1 and the associated inflammatory factor IL-10. These effects are blocked by the administration of the γ-secretase inhibitor DAPT, a specific blocker of the Notch signaling pathway. LXA4 inhibits the microglia activation induced by LPS and the differentiation into M1 type with pro-inflammatory effect, while promoting the differentiation to M2 type with anti-inflammatory effect. LXA4 downregulates the inflammatory mediators IL-1β, TNF-α, and iNOS, while upregulating the anti-inflammatory mediator IL-10, which acts through the Notch signaling pathway.